2012
DOI: 10.1177/875687051203100102
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Perceived Support to Satisfaction and Commitment for Special Education Teachers in Rural Areas

Abstract: This study examined the relationship of work-related support to teacher satisfaction and job commitment for rural special educators. The researcher conducted a phone survey with 203 special education teachers from randomly selected rural districts in 33 states. The results suggest that several key sources of support, such as support from other special educators, are of limited availability. Teachers who reported a wider network of support, and that sources of support were helpful expressed greater levels of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 24 publications
2
63
2
5
Order By: Relevance
“…As teachers and districts struggled to continue to provide a free and appropriate public education for their students, two LICs described their efforts to support teachers. While researchers have noted that teacher support is important for retention of rural special education teachers (N. Barrett et al, 2015) and have identified areas of support needs (Berry, 2012;Berry et al, 2011), there is little guidance in the literature on how to provide teacher support in the face of a crisis of this magnitude. The LICs noted that the districts who had NTI approval prior to the pandemic appeared to be better prepared to provide instruction because they had experienced using similar formats for the short term (e.g., due to illness or weather-related events).…”
Section: Discussionmentioning
confidence: 99%
“…As teachers and districts struggled to continue to provide a free and appropriate public education for their students, two LICs described their efforts to support teachers. While researchers have noted that teacher support is important for retention of rural special education teachers (N. Barrett et al, 2015) and have identified areas of support needs (Berry, 2012;Berry et al, 2011), there is little guidance in the literature on how to provide teacher support in the face of a crisis of this magnitude. The LICs noted that the districts who had NTI approval prior to the pandemic appeared to be better prepared to provide instruction because they had experienced using similar formats for the short term (e.g., due to illness or weather-related events).…”
Section: Discussionmentioning
confidence: 99%
“…The differences relate, for example, to the environment; the student body; the number of students, teachers and support staff; the organisation of instruction; and professional development opportunities. Although rural communities and rural schools differ across, as well as within, countries, rural researchers have identified some common rural school features, namely, geographic isolation, a low number of teachers and students, multi‐grade classrooms, diverse learning needs among students, lack of support staff, multifaceted working tasks for teachers and scarce professional development opportunities (Bæck, ; Berry, ; Kalaoja & Pietarinen, ; Kvalsund, ; Malloy & Allen, ; Sörlin, ; Åberg‐Bengtsson, ). Other challenges faced by rural schools include ongoing demographic and social changes, shrinking population, financial constraints and the constant fear of school closures (Autti & Hyry‐Beihammer, ; Egelund & Laustsen ; Hargreaves, ; Kearns et al, ; Uba, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional teacher–working environment fit (i.e. professional recognition and constructive work climate) may act as a buffer against special education teachers’ risk of developing burnout, and hence contribute to the meaningful and sustainable pedagogical development of the school community (Sutherland et al ., ; Berry, ; Conley & You, ; Pietarinen et al ., ; Berkovich & Eyal, ). Even though special education teachers have a crucial role in supporting an inclusive learning environment in school, there is a dearth of literature about their experiences, despite the focus on strong inclusion policies in many countries (see the review study by Brunsting et al ., ).…”
Section: Introductionmentioning
confidence: 99%